Interaction between children in the third cycle of EBR to strengthen coexistence in the classroom of a school located in Ventanilla, Callao - Prado Herrera, Reyna (2021)
The objective of this research was to analyze the modes of socialization of first and second grade students of an educational institution for a harmonious coexistence. The study is of a mixed, descriptive and non-experimental nature. The information collection was carried out considering three categories: modes of interaction, types of student games, and common conflicts through the techniques of observation, interview and survey. From the analysis of the findings, it was identified that the interaction between the students is mainly aggressive; the most common types of play are "chapadas", fights and lying one under the other, most of which include acts of violence; and more recurrent conflicts lead to hitting and shoving situations.